POLYMORPHISM STEAROYL-COA DESATURASE (SCD) GENE AND ASSOCIATON WITH CHARACTERISTICS MEAT IN BALI CATTLE - Alwiyah, A.; Naraini, H.; Agung, P. P.; Jakaria, J. (Journal of the Indonesian Tropical Animal Agriculture, 2016)
Stearoyl-CoA desaturase (SCD) is an enzyme produced by SCD gene which is responsible for a conversion of saturated fatty acids (SFA) to mono-unsaturated fatty acid (MUFA) in adipose tissue. This enzyme affects the fats in intramuscular so having influence on marbling. The purpose of this study was to obtain the polymorphisms of the SCD gene and their associations with meat quality traits in Bali cattle. The number of samples used were 48 heads of cattle consisted of 24 bulls and 24 cows from BPTU-HMT Bali cattle in the province of Bali. The SCD gene has been amplified using forward primer 5’-ACC CCT TGG TGT GTG GTT GTT CTT C-3 ‘and reverses primer 5'-CCT GAC GAT ACT ATG TTT CTA CTT C-3'. The polymorphisms of the SCD gene were identified by direct sequencing method. Meat quality traits such as thick of longissimus dorsi (TLD), thick of back fat (TBF), thick of fat rump (TFR), thick of rump (TR), marbling score (MS), and the percentage of intramuscular fat (PIMF) were analyzed using the Veterinary Ultrasound Scanner. To determine Hardy-Weinberg equilibrium status, both allele and genotype frequencies were analyzed using GENEPOP program (V3.2). Association of the SCD gene SNP and meat quality traits was analyzed by GLM. This result showed that there were 5 monomorphic SNPs (c.10153A>G, c.10318C>A, c.10329C>T, g.10394G>A, g.10486A>C) and 3 polymorphic SNPs (g.10360G>A, g.10428C>T, g. 10487G>A) were in HW equilibrium. Association analysis showed that g.10428C>T SNP significantly affected marbling score (MS) and percentage of intramuscular fat (PIMF) (P<0.05). Based on these results, g.10428C>T SNP of the SCD gene may be used as a candidate marker to select meat quality traits in Bali cattle.